Efficacy and Safety of Prolonged Magnesium Sulfate Infusions in Children With Refractory Status Asthmaticus - Taher, Khalid W.; Johnson, Peter N.; Miller, Jamie L.; Neely, Stephen B.; Gupta, Neha (Frontiers in Pediatrics, 2022)
OBJECTIVES: There is a paucity of data on the use of intravenous magnesium sulfate infusion in children with refractory status asthmaticus. The purpose of this study was to evaluate the efficacy and safety of prolonged magnesium sulfate infusion as an advanced therapy. METHODS: This is a single-center retrospective study of children admitted to our pediatric intensive care unit (PICU) with status asthmaticus requiring continuous albuterol. Treatment group included patients receiving magnesium for >4 hours and control group included those on other therapies only. Patients were matched 1:4 based on age, sex, obesity, pediatric index of mortality III and pediatric risk of mortality III scores. Primary outcomes included PICU length of stay (LOS) and mechanical ventilation (MV) requirement. Secondary outcomes included mortality, extracorporeal membrane oxygenation (ECMO) requirement, analyses of factors associated with PICU LOS and MV requirement and safety of magnesium infusion. Logistic and linear regressions were employed to determine factors associated with MV requirement and PICU LOS respectively. RESULTS: Treatment and control groups included 27 and 108 patients, respectively. Median initial infusion rate was 15mg/kg/hour, with median duration of 28 hours. There was no difference in the MV requirement between the treatment and control groups [7 (25.9%) versus 20 patients (18.5%), p=0.39]. Median PICU LOS and ECMO use were significantly higher in treatment versus control group [(3.63 versus 1.09 days, p<0.01) and (11.1% versus 0%, p<0.01) respectively]. No mortality difference was noted. On regression analysis, patients receiving ketamine and higher prednisone equivalent dosing had higher odds of MV requirement [OR 19.29 (95% CI 5.40-68.88), p<0.01 and 1.099 (95% CI 1.03-1.17), p<0.01 respectively] . Each mg/kg increase in prednisone equivalent dosing corresponded to an increase in PICU LOS by 0.13 days (95% CI 0.096-0.160, p<0.01). Magnesium infusions were not associated with lower MV requirement or lower PICU LOS after controlling for covariates. Fourteen (51.9%) patients in the treatment group had an adverse event, hypotension being the most common. CONCLUSION: Magnesium sulfate infusions were not associated with MV requirement, PICU LOS or mortality.